2022
DOI: 10.1155/2022/8856025
|View full text |Cite|
|
Sign up to set email alerts
|

The Current Antimicrobial and Antibiofilm Activities of Synthetic/Herbal/Biomaterials in Dental Application

Abstract: Herbal and chemical products are used for oral care and biofilm treatment and also have been reported to be controversial in the massive trials conducted in this regard. The present review is aimed at evaluating the potential of relevant herbal and chemical products and comparing their outcomes to conventional oral care products and summarizing the current state of evidence of the antibiofilm properties of different products by evaluating studies from the past eleven years. Chlorhexidine gluconate (CHX), essen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 183 publications
0
22
0
Order By: Relevance
“…Written resources alone appear insufficient to understand sophisticated dentistry and oral and maxillofacial surgery techniques. The previous studies have shown that mastering basic practical skills reduce patient injury risks [12], [15], [16], [17], [18], [19], [20], [21], [22], [23].…”
Section: Discussionmentioning
confidence: 99%
“…Written resources alone appear insufficient to understand sophisticated dentistry and oral and maxillofacial surgery techniques. The previous studies have shown that mastering basic practical skills reduce patient injury risks [12], [15], [16], [17], [18], [19], [20], [21], [22], [23].…”
Section: Discussionmentioning
confidence: 99%
“…This review discussed the importance of prosthetic restorative materials on the state of the periodontium, as well as the changes that occur in the composition of the subgingival microbiota and the levels of inflammatory markers in the gingival crevicular fluid. Today, new materials are being sought that exert less of an inflammatory response in the tissues, while still meeting the esthetic and strength requirements, which are important for restoring the oral cavity to a good level of health, esthetics and function [ 14 , 174 , 175 , 176 ].…”
Section: Future Perspectivesmentioning
confidence: 99%
“…Dental procedures lead to the dissemination of microorganisms in the aerosol in the dental office. Some research showed mouth wash rinse such as chlorhexidine, essential oils, cetylpyridinium chloride, and herbal products to reduce the microorganisms in dental office aerosol [37], [38], [39], [40], [41], [42], [43], [44], [45], [46], [47], [48]. Commercially available mouthwashes, such as 0.05% cetylpyridinium chloride CPC utilized as a pre-procedural mouth rinse, were equally beneficial, as CHX, to lower the incidence of bacteria produced during the ultrasonic scaling [39], [40], [44], [49], [50], [51], [52].…”
Section: Mouth Washmentioning
confidence: 99%